From Typology to Taxonomy: A Configurational Analysis of National Business Systems and their Explanatory Power. Issue 5 (May 2014) - Hotho, Jasper J.
The business systems approach holds considerable promise for improving our understanding of the relations between societal institutions and technological and economic outcomes. Nonetheless, there have been surprisingly few attempts to validate its proposed typology of business system types. In this paper, I take up this issue and conduct a large-scale empirical assessment of the national business systems typology. I use data on 30 OECD countries from 2000 and 2011 to assess the validity of the typology, and explore its value for comparative institutional analysis through a fuzzy-set analysis of innovation specialization patterns. The findings illustrate that while the national business systems typology needs to be extended, it remains relevant for describing variety in national institutional frameworks. In addition, the detail it adds may provide the nuance needed for exploring more complex relations between institutions and technological and economic outcomes.